Highlights mild traumatic brain injury 2021. Issue 5 (4th August 2022) - van der Naalt, Joukje; Jacobs, Bram
Abstract : Purpose: Mild traumatic brain injury (TBI) is one of the most common causes of morbidity worldwide. Patients at risk of unfavourable outcome may benefit from additional attention and help but identification of these patients necessitates the development of diagnostic methods to assess indices of brain injury at an early stage. The aim of this overview is to highlight studies that reflect the growing scientific attention to the early diagnosis and prognostication of mild TBI. Recent findings: The value of serum biomarkers for the diagnosis of TBI severity has been acknowledged in recent studies. The diagnostic and prognostic utility of several biomarkers of brain injury, such as glial fibrillary acidic protein, and of inflammation, such as interleukin (IL)-6 and IL-10, holds promise for application in daily clinical practice in a point-of-care platform. Besides head CT imaging, early advanced MRI brain imaging has been reported as a tool for assessment of injury severity and prognostication. The introduction of direct oral anticoagulants (DOACs) has raised new challenges for the treatment of intracranial traumatic haemorrhage at the Emergency Department. Summary: Promising findings of new diagnostic markers of brain injury severity highlight the potential prognostic value of serum biomarkers and early MRI imaging. The accurate assessment of patients at risk of incomplete recovery after mTBI will enhance more timely and individualized treatment.